A mulher Tapuya e seu cão – Notas sobre as relações entre indígenas e cachorros no Brasil holandês - Felipe Vander Velden (Centre de Recherches sur les Mondes Américains, 2019)
The presence of a dog drinking water at the feet of the Dutch painter Albert Echkout’s famous Tapuya Woman has long been associated with the symbolism of the primitive, savage and uncultured Indian that the artist probably wished to convey, following pictorical conventions of the seventeenth century. However, the canine companion of this indigenous woman, if handled in parallel with a few other sources available for the same period, reveals some interesting clues about the rapid diffusion of the dog (Canis familiaris) among the indigenous peoples in the eastern portion of South America, where the animal did not exist in pre-Columbian times. Moreover, the images and texts allow us to speculate on the initial moments of the relationships between humans and dogs in lowland South America, thus going beyond the pervasive allegorical tenor attributed to the animal.